Readiness for Change in Business Contexts: A Systematic Literature Review - Frank VOGGENREITER; Margarida M. PINHEIRO; Rui Pedro MARQUES (Communications of International Proceedings, 2023)
Change in business organizations often leads to suffering individuals. For organizations, it remains difficult to find guidance on how to reduce this pain. The purpose of this paper is to provide a Systematic Literature Review (SLR) on the topic of Readiness for Change (RfC) in business contexts, a topic that is been gaining importance during the last decade. The specific objective is to collect and list all antecedents of RfC. Data is collected from the Web of Science. SLR procedures are used, starting with a search protocol and validated by two independent researchers. The final selection of 79 articles is analyzed per year, journal, author, country, and area. The review articles are exported to NVivo for full content analysis and coding. An overview of all antecedents of RfC, as well as a structured categorization of the published reviewed papers is presented. This article presents empirical evidence on the state-of-the-art in RfC including a list of antecedents of change. Knowledge transfer is recognized as one key antecedent of RfC. This work has policy-setting implications for understanding the RfC process and its antecedents. It can also help organizations prepare, anticipate, and minimize the impact of negative organizational change.
Keywords: Change Readiness; Literature Review; State-of-the-art